Patient values informing medical treatment: a pilot community and advance care planning survey - Milnes, S; Corke, C; Orford, N; Bailey, M; Savulescu, J; Wilkinson, D (BMJ Publishing Group, 2017)
Medicine regards the prevention of death as an important priority. Yet patients may have a range of priorities of equal or greater importance. These other priorities are often not discussed or appreciated by treating doctors. Objectives We sought to identify priorities of care for patients attending an advance care planning (ACP) clinic and among the general population, and to identify factors associated with priorities other than prolonging life. Methods We used a locally developed survey tool ‘What Matters Most’ to identify values. Choices presented were: maintaining dignity, avoiding pain and suffering, living as long as possible, and remaining independent. Participants rated the importance of each and then selected a main priority for their doctor. Participant groups were a purposive sample of 382 lay people from the general population and 100 attendees at an ACP clinic. Results Living as long as possible was considered to be less important than other values for ACP patients and for the general population. Only 4% of ACP patients surveyed and 2.6% of our general population sample selected ‘living as long as possible’ as their top priority for medical treatment. Conclusions ‘Living as long as possible’ was not the most important value for ACP patients, or for a younger general population. Prioritisation of other goals appeared to be independent of extreme age or illness. When end of life treatment is being discussed with patients, priorities other than merely prolonging life should be considered.